2005
DOI: 10.1002/cncr.20886
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome after breast‐conservation treatment with radiation for mammographically detected ductal carcinoma in situ of the breast

Abstract: BACKGROUNDDuctal carcinoma in situ (DCIS) is detected most commonly on routine screening mammography in the asymptomatic patient, and has a long natural history. The objective of the current study was to determine the long‐term outcome after breast‐conservation surgery followed by definitive breast irradiation for women with mammographically detected DCIS of the breast.METHODSIn total, 1003 women with unilateral, mammographically detected DCIS of the breast underwent breast‐conserving surgery followed by defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
98
4
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(116 citation statements)
references
References 78 publications
8
98
4
6
Order By: Relevance
“…At a median follow-up of 8.5 years there were only 100 LRs in the treated breast, yielding a 10-year actuarial LR rate of 10%. 19 The experience of the Institute Curie over a 30-year period (1967 to 1996) was reported. 20 Among 601 DCIS patients, 343 were treated with wide excision plus RT.…”
Section: Discussionmentioning
confidence: 99%
“…At a median follow-up of 8.5 years there were only 100 LRs in the treated breast, yielding a 10-year actuarial LR rate of 10%. 19 The experience of the Institute Curie over a 30-year period (1967 to 1996) was reported. 20 Among 601 DCIS patients, 343 were treated with wide excision plus RT.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Solin et al, patients with comedoarchitecture and nuclear grade 3 had a significantly higher 5-year LR rate; the difference was no longer statistically significant at 10 years. (28) In the EORTC trial multivariate analysis at a median follow-up of 10.5 years, intermediately or poorly differentiated DCIS had a significantly increased risk for LR as opposed to well differentiated DCIS (HR = 1.85 and HR = 1.61 respectively). (29) In the updated multivariable analysis performed at 15 years, nuclear grade was not an independent risk factor for local recurrence.…”
Section: Nuclear Gradementioning
confidence: 98%
“…At present, young age per se should not be a contraindication for BCT, especially because it is unknown whether these patients have a superior long-term prognosis if treated by mastectomy. Local recurrences followingboth skin sparing and simple-mastectomy after DCIS are reported and also seem to occur particularly in younger women (12,13).Numerous studies have shown an increased risk of local recurrence when DCIS was excised with doubtful or involved margins (2,6,7,14,15). Various thresholds have been reported as a safe margin status, from "the inked margin not being involved with DCIS," to ≥1, 2, 3, or 5 mm, or even ≥1 cm.…”
mentioning
confidence: 99%
“…Age and margin status are the most important factors related to the risk of local recurrence. The impact of young age on the outcome of treatment of DCIS has been studied by several groups (2,(6)(7)(8)(9). In the EORTC 10853 trial, women aged 40 years or younger had a 34% risk of local recurrence at 10 years compared with 19% of the women older than 40 years ( Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation